Repetitive saliva swallowing test and water swallowing test may identify a COPD phenotype at high risk of exacerbation. (19th March 2019) - Yoshimatsu, Yuki; Tobino, Kazunori; Sueyasu, Takuto; Nishizawa, Saori; Goto, Yuki; Murakami, Kojin; Munechika, Miyuki; Yoshimine, Kohei; Miyajima, Hiroyuki
Abstract: Introduction: Patients with chronic obstructive pulmonary disease (COPD) are known to present with dysphagia from an early stage. Dysphagia leads to swallowing‐related complications, in turn leading to COPD exacerbation. Dysphagia screening is recommended; however little is known of its utility in detecting a COPD phenotype at risk for exacerbation. The simple swallowing provocation test (SSPT), considered to be a standard screening test, requires specific equipment, physician skill and patient discomfort. Objectives: The aim of this study was to find an easier and less invasive measure to screen for dysphagia in patients with COPD. Methods: We retrospectively reviewed patients with COPD who were screened for dysphagia [Repetitive saliva swallowing test (RSST), water swallowing test (WST), SSPT and a questionnaire] from June to November 2016. The patients were classified into two groups according to the presence of COPD exacerbation in the past 3 years (ie, exacerbation and non‐exacerbation group), and the dysphagia screening results were compared between the groups. Results: Of the 80 cases included, 42 had 1 or more exacerbations in the past 3 years (exacerbation group), and 38 had none (non‐exacerbation group). Statistically significant differences between the groups were observed in the RSST, and vocal change in the WST ( P < 0.05). There were no significant differences between the groups in the results of SSPT, COPD stage and other clinical status. Conclusions: Compared to the SSPT, RSST and WST may be more appropriate screening methods in patients with COPD. A prospective study is necessary for further assessment.